2015
DOI: 10.1007/s10571-015-0225-3
|View full text |Cite|
|
Sign up to set email alerts
|

Upregulation of miR-107 Inhibits Glioma Angiogenesis and VEGF Expression

Abstract: MicroRNAs can function as oncogenes or tumor suppressors in glioma. Previously, we showed that miR-107 inhibits glioma cell proliferation, migration, and invasion. Since tumor growth and invasion are closely related to angiogenesis, we further examined the role of miR-107 in glioma angiogenesis. In a co-culture of glioma cells and human brain microvascular endothelial cells (HBMVEC), overexpression of miR-107 in glioma cells led to the inhibition of HBMVEC proliferation, migration, and tube formation ability. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…They affected the genesis of glioma and enhanced multifaceted biological capabilities by promoting angiogenesis and prognosis (Hara and Okayasu, 2004). Western blotting assay of COX-2, iNOS and VEGF did not totally prove the anti-angiogenesis function of AVNP2 on gliomas but gave us a hint, which needs to be investigated deeper by means of ELISA and the tubule formation test in vivo and in vitro (Chen et al, 2016). The activation or suppression of endothelial cells (ECs), which play an important part in tumour angiogenesis, are worthy of study and discussion too (Liu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…They affected the genesis of glioma and enhanced multifaceted biological capabilities by promoting angiogenesis and prognosis (Hara and Okayasu, 2004). Western blotting assay of COX-2, iNOS and VEGF did not totally prove the anti-angiogenesis function of AVNP2 on gliomas but gave us a hint, which needs to be investigated deeper by means of ELISA and the tubule formation test in vivo and in vitro (Chen et al, 2016). The activation or suppression of endothelial cells (ECs), which play an important part in tumour angiogenesis, are worthy of study and discussion too (Liu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the function of miR-107 in cancer, reduced miR-107 expression has been reported in various types of cancer 6978 , and several recent studies have identified the tumor suppressor functions of miR-107. One crucial function of miR-107 that has been identified is the inhibition of oncogenes, such as CDK8 in breast cancer 71 , the ATR/Chk1 pathway in cervical cancer 79 , HIF-1, CCND1, and NFKB1 in colon cancer 80, 81 , CDK in gastric cancer 70 , CDK6, Notch-2, and VEGF in glioma 74, 75, 82, 83 , CDK6 and CDK8 in non-small cell lung cancer 84, 85 , GRN in prostate cancer 78 , eukaryotic translation initiation factor 5 in renal clear cell carcinoma 86 , and CDK6 in PCa 87 . Furthermore, some studies have demonstrated that the tumor suppressor p53 inhibits tumor angiogenesis and cell growth through the transcriptional regulation of miR-107 in several cancer types 74, 80 .…”
Section: Discussionmentioning
confidence: 99%
“…As expected, one of the control levels is transcription-related to the interaction between IL-8 and VEGF promoters and different transcription factors, such as NF-κB, AP-1 and C-EBP/NF-IL-6 (7)(8)(9)(10)(11)(12). In addition, the expression of IL-8 and VEGF genes may be under the control of epigenetic mechanisms, such as those regulated by microRNAs in cancer, differentiation and inflammatory processes (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%